Long-term intensive golf training induces reconfiguration of brain structural covariance networks - Zonghan Lei; Yaoqi Hou; Xiangqin Song (PLoS ONE, 2026)
Long-term motor training is thought to reshape brain organization, yet how golf expertise influences large-scale brain networks remains unclear. Using T1-weighted MRI and an individualized structural covariance network (SCN) approach, we compared 20 expert golfers, 20 novice golfers, and 20 non-golfer controls. Experts showed higher global clustering coefficient and local efficiency than novices, indicating enhanced modular processing. At the nodal level, experts exhibited increased clustering in regions supporting visual–sensorimotor integration (e.g., right supramarginal gyrus, Heschl’s gyrus, and left middle temporal pole), alongside reduced global efficiency in the left calcarine cortex and altered path length in the right cerebellum. Importantly, the clustering coefficient mediated the association between training duration and stroke accuracy. These cross-sectional findings suggest that extensive golf training is linked to a brain network reconfiguration that favors local specialization over global integration—potentially supporting the refined sensorimotor control required in elite performance. This study advances understanding of experience-dependent neuroplasticity by integrating individualized network analysis with behavioral outcomes in motor expertise.